Philosophy of Islamic Education: an Analysis of Nomenclature Disputes Through Historical, Anagogical, and Philosophical Perspectives - Fitryansyah, Muhammad Andryan (STAI Asy-Syukriyyah, 2024)
This research examines nomenclature disputes in Islamic Philosophy of Education using historical, anagogical and philosophical approaches. The research question posed is how the disputes over terms such as 'tarbiyah', 'ta'lim' and 'ta'dib' reflect different views within the Islamic educational tradition and what the philosophical and spiritual implications are. The aim of this study is to provide a deeper understanding of the evolution and meaning of these terms and their contribution to the discourse of Islamic education. The method used is an in-depth literature analysis with a qualitative approach, combining a historical study to trace the development of the terms, an anagogical analysis to unearth their spiritual meaning, and a philosophical approach to explore their conceptual implications. The results show that the nomenclature disputes not only reflect intellectual diversity in Islam but also highlight the need for a more holistic and multidimensional approach in understanding Islamic education. This research contributes to the development of a more inclusive Islamic education discourse that is relevant to the contemporary context.